POSSIBLE TOURISM AND POSSIBILITIES DEVELOPMENT IN BUKHARA AREA - Turobovna, Jurayeva Zilola; Hamidovich, Ziyavitdinov Habibullo (International Journal of Psychosocial Rehabilitation, 2020)
This article explains the importance and objective importance of tourism in the development of the national economy. The tourist potential and opportunities of the Republic of Uzbekistan are described. It also describes the nature and importance of "pilgrimage tourism", which is developing today among the types of tourism. In Uzbekistan, in particular, the objects of tourist tourism in Bukhara region, their history and opportunities for the development of pilgrimage tourism in the region.